Learning in the clinical skills and simulation centre University of Ghana : medical students’ experiences of teaching sessions : an exploratory study - Muniru, Ayishetu (Stellenbosch : Stellenbosch University, 2016)
Thesis (MPhil)--Stellenbosch University, 2016